Secure rail station – Research on the effect of security checks on passenger flow. (August 2019) - Asmer, Lukas; Popa, Andrei; Koch, Tobias; Deutschmann, Andreas; Hellmann, Martin
Abstract: The threat of international terrorism is becoming increasingly evident in Europe. Especially critical infrastructures, such as transport infrastructures, are in focus of terrorist attacks. Therefore, we conduct a feasibility study on the introduction of security checks at train stations. A simulation model for Brunswick, Germany train station has been created and used to investigate the impact of additional security checks on the passenger flow. Several simulations with a varying number of opened security checks were carried out and data for queue length, waiting times and passengers reaching their train in time was analyzed. The simulations have shown that it would be possible to sustain passenger processing at Brunswick railway station with regional and long-distance connections using considerable resources (up to 18 security checkpoints). With fewer than 18 checkpoints, a scheduled, traffic-oriented processing of the passengers is not possible. However, local traffic would significantly lose convenience as a means of transport, since many passengers would have to expect long waiting times despite short travel distances. A possible concept could therefore be a separation of regional and long-distance traffic by the introduction of so-called satellite railway stations in metropolitan areas. Highlights: Introduction of security checks causes a bottleneck effect. Very high waiting times during peak hours at security checks. Many passengers miss their trains due to high waiting times at security checks. Change of arrival times nearly has no influence on passengers missing trains. Introduction of security checks at rail stations connected to high resource demand.